Sexuality and religion - Izquierdo Mitjáns, Yesmín (Pensando Psicología, 2010)
This article expose the refl ection about the results of a case study of Christian couples, which revealed that they share many assumptions about the relationship, gender roles and sexual practices. A look at these results reveals how sexuality is repressed in these individuals, not only in the context of the relationship, but also personally. On this occasion, a socio-historical and cultural commonalities of those found, reveals that - after so many vicissitudes that have befallen the human sexuality - you may have established these religious militants in a special relationship between sexuality and religion concepts. Relationship can become an explanation about the situation such couples still living in the sexual sphere.
Keywords: sexuality; religion; matrimonial relationship